Expanding biohybrid-mediated asymmetric catalysis into the realm of RNA. Issue 55 (21st June 2016) - Duchemin, Nicolas; Benedetti, Erica; Bethge, Lucas; Vonhoff, Stefan; Klussmann, Sven; Vasseur, Jean-Jacques; Cossy, Janine; Smietana, Michael; Arseniyadis, Stellios
Abstract : We report here the first example of an RNA-based catalyst involving a catalytically active metal complex interacting in a non-covalent fashion with short RNA sequences. Abstract : The recent development of biohybrid catalytic systems has allowed synthetic chemists to reach high levels of selectivity on a wide variety of valuable synthetic transformations. In this context, DNA-based catalysts have emerged as particularly appealing tools. Interestingly, while long RNA sequences (ribozymes) are known to catalyse specific biochemical reactions with remarkable efficiencies, RNA-based catalysts involving a catalytically active metal complex interacting in a non-covalent fashion with short sequences have never been evaluated to date. We report here our results, which have led to the first example involving a short RNA-based catalyst.